Relationships between older adults' use of time and cardio-respiratory fitness, obesity and cardio-metabolic risk: A compositional isotemporal substitution analysis. (April 2018) - Dumuid, D.; Lewis, L.K.; Olds, T.S.; Maher, C.; Bondarenko, C.; Norton, L.
Highlights: How older adults use their time is related to their fitness and adiposity. More moderate-to-vigorous physical activity, at the expense of other behaviours, is linked to lower adiposity. Maintaining moderate-to-vigorous physical activity, even without increasing it, may be a valuable intervention goal. Abstract: Objective: Older adults' health has been linked with time in moderate-to-vigorous physical activity (MVPA), and recent studies suggest time in sedentary behaviour may also be important. Time-use behaviours (MVPA, light physical activity, sedentary time and sleep) are co-dependent, and therefore their associations with health should be examined in an integrated manner. This is the first study to investigate the relationship between older adults' reallocation of time among these time-use behaviours and markers of cardio-respiratory fitness, obesity and cardio-metabolic risk. Study design: Cross-sectional study of 122 Australians (65 ± 3 y, 61% female). Main outcome measures: Daily time use: average daily minutes spent in MVPA, light physical activity, sedentary time and sleep derived from 24-h, 7-day accelerometry, were conceptualised as a time-use composition. Cardio-respiratory fitness: graded submaximal cycle ergometer test. Obesity: objectively measured body mass index (BMI) and waist-to-hip ratio (WHR). Cardio-metabolic risk: sphygmomanometer-measured resting blood pressure and fingertip blood sampling for fasting total cholesterol and glucose. Results: Time-use composition was significantly associated with obesity markers (BMI, p = 0.001; WHR, p < 0.001). The reallocation of 15 min to MVPA from any of the other behaviours was associated with approximately +1.1 (95% confidence interval 0.2; 1.9) ml/kg −1 min −1 VO2max, −0.7 (−1.0; −0.3) BMI units and −1.2 (−1.8; −0.7) WHR percentage points, while the opposite reallocation (15 min from MVPA to other behaviours) was associated with larger difference estimates of −1.8 (−3.2; −0.4) ml/kg −1 min −1 VO2max, +1.2 (0.5; 1.9) BMI units and +2.1 (1.2; 3.1) WHR percentage points. Conclusion: These findings reinforce the importance of MVPA for health among older adults. Interventions to maintain MVPA, even without increasing it, may be valuable.